Statement by the Managing Director on the Independent Evaluation Office's Report on the IMF and the Crises in Greece, Ireland, and Portugal : An Evaluation by the Independent Evaluation Office. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
I welcome the report of the Independent Evaluation Office (IEO) on the Euro Area crisis programs. Their work provides an independent and in-depth account, which I have no doubt will make an important contribution to understanding the Fund's approach to the crisis. As I have emphasized repeatedly, the IEO plays a vital role in enhancing the learning culture within the Fund, strengthening the Fund's external credibility, and supporting the Executive Board's institutional governance and oversight responsibilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Crisis Program; Crisis; Fund; Policy; PP; Greece